INFLATION IN F(R, T) GRAVITATION WITH f-ESSENCE - Myrzakul, S.R.; Myrzakulov, Y.M.; Arzimbetova, М. (Academic Scientific Journal of Computer Science, 2020)
Modified theories of gravity have become a kind of paradigm in modern physics because they seem to solve several shortcomings of the standard General Theory of Relativity (GTR) related to cosmology, astrophysics and quantum field theory. The most famous modified theories of gravity are F(R) and F(T) theories of gravity. A generalization of these two modified theories and gravitations, which was first proposed by Myrzakulov Ratbay. In this paper, we study an inhomogeneous isotropic cosmological model with a fermion field f-essence whose action has the form where R is the scalar of curvature, and T is the torsion scalar, and Lm is the Lagrangian f-essence. A particular case is studied in detail when parameters are obtained that describe the current accelerated expansion of the Universe. The type of Lagrangian f-essence of this model is determined. The presented results show that gravity with f-essence can describe inflation in the early evolution of the Universe. A modified F(R, T) gravity with f-essence is considered. Equations of motion were obtained and the inflationary period of the early Universe was considered. To describe the inflationary period, the form of the Hubble parameter and the slow-roll parameter were determined.